ATM networks and cash usage - Heli Snellman; Matti Virén (Bank of Finland, 2006)
This paper deals with the issue of how the market structure in banking affects the choice of means of payment.In particular, the demand for cash is analysed from this point of view.The analysis is based on a simple spatial transactions model in which the banks' optimization problem is solved.The solution quite clearly shows that monopoly banks have an incentive to restrict the number of ATMs to a minimum.In general, the number of ATMs depends on competitiveness in the banking sector.The predictions of the theoretical analysis are tested using panel data from 20 OECD countries for the period 1988-2003.Empirical analysis reveals that there is a strong and robust relationship between the number of ATM networks and the number of ATMs (in relation to population).It also reveals that the demand for cash depends both on the number of ATMs and ATM networks and on the popularity of other means of payment.Thus, the use of cash can be fairly well explained in a transaction demand framework, assuming proper controls for market structure and technical environment.
URN:NBN:fi:bof-20140807138
Keywords: E41; E51; 330; automated teller machine; demand for cash; banking; means of payment